18FDG PET/CT in Primary Cutaneous Diffuse Large B-Cell Lymphoma Leg Type. (May 2020) - Dejust, Sébastien; Morland, David; Durot, Eric; Grange, Florent; Papathanassiou, Dimitri
Abstract : Abstract: An 86-year-old woman was referred for a rare but aggressive subtype of primary cutaneous lymphoma of the right lower limb: diffuse large B-cell lymphoma leg type. Initial evaluation by whole-body 18 F-FDG PET/CT showed intense hypermetabolic activity of multiple cutaneous and subcutaneous nodules of the distal third of the right leg. Follow-up evaluations by 18 F-FDG PET/CT showed complete response after 4 and 8 cycles of appropriate rituximab combination with polychemotherapy. Although no specific recommendations are available, our case stresses the major role of 18 F-FDG PET/CT for initial extension and treatment response evaluation in clinical practice of primary cutaneous diffuse large B-cell lymphoma leg type.